2019
DOI: 10.1111/tme.12633
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of periodontitis in blood donors and the possibility of questionnaire‐based screening – results of a cross‐sectional study

Abstract: Background:Periodontitis is an inflammatory disease of high prevalence and, thus, of potential relevance to the management of blood donation. Objectives:The aim of this cross-sectional study was to assess periodontal health and its associations to common blood parameters, as well as questionnaire-based periodontitis screening in blood donors. Methods:Generally healthy blood donors were recruited and underwent oral examination. Thereby, the decayed-, missingand filled-teeth index (DMF-T) and periodontal status,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
0
5
0
1
Order By: Relevance
“…In addition, the relationship between periodontal and systemic inflammation might be addressed in future research. This could be of certain interest for patients with LVAD, although the effect of periodontitis on systemic parameters of inflammation in general is limited . Beside of these limitations, the current study provides new knowledge of clinical relevance for the care of LVAD patients.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, the relationship between periodontal and systemic inflammation might be addressed in future research. This could be of certain interest for patients with LVAD, although the effect of periodontitis on systemic parameters of inflammation in general is limited . Beside of these limitations, the current study provides new knowledge of clinical relevance for the care of LVAD patients.…”
Section: Discussionmentioning
confidence: 98%
“…Standardized questionnaires about oral health behavior and periodontal symptoms were used as established in various previous studies by this working group 34–36 . All athletes were asked to complete them self‐administered on‐site.…”
Section: Methodsmentioning
confidence: 99%
“…Standardized questionnaires about oral health behavior and periodontal symptoms were used as established in various previous studies by this working group. [34][35][36] All athletes were asked to complete them self-administered on-site. Questions were asked about dentist visits (control or complaint-oriented check-ups, regular professional teeth cleaning), the importance of oral health, oral hygiene behavior (frequency of toothbrushing, interdental hygiene, use of fluoride gels), and received instructions about oral hygiene.…”
Section: Questionnairesmentioning
confidence: 99%
“…Further biological mechanisms are cross-reactions caused by bacterial or inflammatory dysregulations of the immune defense with resulting autoaggression, and the swallowing and aspiration of bacteria [45,46] are further biological mechanisms. Some studies found respective differences in blood parameters for patients with periodontitis, while others did not [47,48]. However, changes in circulating blood cell profiles [32] and increasing CRP values [49] are reported by recent systematic reviews and seem to reflect the systemic inflammatory reaction.…”
Section: Impact Of Oral Inflammation On General Healthmentioning
confidence: 98%